2008
DOI: 10.4314/sajas.v38i1.4108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant age on the chemical composition of fresh and ensiled <i>Agave salmiana</i> leaves

Abstract: In the first study dry matter (DM), organic matter, crude protein (CP), neutral detergent fibre (NDF) and soluble carbohydrate (SC) concentrations were determined in whole leaves and the upper and lower sections of whole leaves of the Agave salmiana (Otto ex. Salm-Dyck) plant. The pH and saponin concentration were measured in aqueous extracts from these leaves. The leaves were collected from plants at the young (ca. 12 years old), bud (ca. 14 years old) and mature (ca. 16 years old) stages of growth. The CP le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
2
11
2
3
Order By: Relevance
“…The total saponin content in IN and EN plants was 7- and 6-times higher in comparison to that reported by Pinos-Rodríguez et al (2008) for 16-year-old plants of A. salmiana (11.1 mg/g dw); however, WT plants from the north of Mexico had a 5-times lower saponin content. The content of saponins is higher in young plants compared with mature or old plants (Francis et al, 2002).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The total saponin content in IN and EN plants was 7- and 6-times higher in comparison to that reported by Pinos-Rodríguez et al (2008) for 16-year-old plants of A. salmiana (11.1 mg/g dw); however, WT plants from the north of Mexico had a 5-times lower saponin content. The content of saponins is higher in young plants compared with mature or old plants (Francis et al, 2002).…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies have shown that the amount of total carbohydrates in Agave sp. increases with the age of the plant (Pinos-Rodríguez et al, 2008) and that these carbohydrates are commonly accumulated as fructans (Arrizon et al, 2010). However, no significant difference in the amount of soluble sugars extracted as fructose and glucose has been reported because these sugars are used by the plant immediately, either for the formation of fructans or for synthesis of sucrose as a transport sugar (Michel-Cuello et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The moisture content of the agave leaves was 86.08 % ± 0.15. This value was close to the one reported for mature agave (89.5 %) without sap extraction (Pinos-Rodríguez et al, 2008). The reduced loss of moisture might be explained by the inherent ability of the plant to retain water (Linton & Nobel, 2001).…”
Section: Chemical Compositionsupporting
confidence: 85%
“…However, the values in all cases were lower than those reported by Simopoulos (2004). These differences could be due to geographical location, plants age, or soil composition as these factors have a great impact on the nutrient contents, phytochemical composition, antioxidant activity, and biological potential of plants (Pinos-Rodríguez et al, 2008;Khattak and Rahman, 2015).…”
Section: Phytochemical Compositioncontrasting
confidence: 45%